Anonymity and learning in digitally mediated communications authenticity and trust in cyber education - Baggio, Bobbe; Beldarrain, Yoany; IGI eBooks; IGI Global (Hershey, Pa. : IGI Global (701 E. Chocolate Avenue, Hershey, Pennsylvania, 17033, USA), 2011)
"This book investigates the impact of anonymity and its effects on online identity and learning, and reveals issues of authenticity and trust, which are at the heart of online learning"--Provided by publisher.
1. The other side of digitally mediated learning -- 2. A code of ethical conduct for global learning -- 3. Intellectual property in an age of open source and anonymity -- 4. E-governance on a global campus -- 5. How safe is your identity? -- 6. Emergence of a new identity -- 7. Academic integrity -- 8. The blending of work, play & learning online -- 9. What was good for the goose is no longer good for the goslings -- 10. Designing for authenticity -- 11. The use of avatars and virtual worlds for learning -- 12. Groups, games & community.
Includes bibliographical references.
Also available in print.
Mode of access: World Wide Web.
Description based on title screen (IGI Global, viewed May 4, 2011).
Keywords: Education -- Computer network resources; Internet in education; Online identities; Internet -- Safety measures; Truthfulness and falsehood; Academic integrity; Avatars; Virtual worlds; Designing for authenticity; E-governance; Emergence of new identities; Ethical conduct; Intellectual property; Open source and anonymity; Security threats; Data mining; Digital fingerprints/footprints; Work, play, and learning online; Electronic books